Water Defluoridation: Nanofiltration vs Membrane Distillation - Morán Ayala, Lucía Isabel (2018)
Nowadays, fluoride contamination of drinking water is a major problem for various countries, because high concentrations of fluoride pose a risk of dental and skeletal fluorosis. Over past years, membrane nanofiltration (NF) has been proposed as convenient defluoridation technology. However, NF cannot be applied to water systems with high fluoride concentration, and the disposal of the membrane concentrate remains an issue. In this work, we compared a commercial polyester NF membrane and a polypropylene hollowfiber membrane distillation (MD) module for their ability to remove fluoride ions from water in the presence of hardness ions and organic fouling agents. The NF membrane can offer more than 10 times higher water productivity than MD, under realistic gradients of temperature and pressure, respectively. Despite that, after reaching a concentration factor of about 3, fouling and scaling caused the flux to drop to about 80% with respect to its initial value. Moreover, F− retention decreased from 90% to below 80%, thus providing a permeate of scarce quality. MD was operated in the direct-contact mode on a polypropylene hollowfiber membrane, which was charged with a hot feed flow (average T = 58 °C) on one side and a cooled (20 °C) permeate flow of distilled water on the other side. The concentration of fluoride ions in the permeate was always below the detection limit of our electrode (0.2 ppm), regardless of the fluoride concentration in the feed. Moreover, the MD module showed higher resistance to fouling and scaling than NF, and CaF2 crystals were recovered from the MD concentrate after cooling. These results suggest that the synergic combination of the two techniques might be beneficial for the purification of fluoridecontaminated water systems: MD can be used to further concentrate the NF retentate, thus producing high-purity water and recovering CaF2 crystals.